Digital transformation model for higher education governance: an integration of business processes, human resources, and technology - Ali Mujahidin; Zuhad Zuhad; Budi Irawanto (Privietlab, 2026)
Digital transformation has become a strategic priority for higher education institutions to improve governance efficiency, service quality, and adaptability in a rapidly evolving digital environment. However, many universities still face challenges due to fragmented administrative processes, limited system integration, and insufficient organizational readiness. This study examines how digital transformation reshapes governance processes through the integration of business processes, human resources, and technological systems. Using a qualitative case study approach, data were collected through semi-structured interviews with six key informants in university management, including the rector, vice rector, IT manager, and academic staff. Data were analyzed using the Gioia methodology to identify emerging patterns. The findings reveal three key dimensions driving digital transformation: business process modernization, organizational and human resource adaptation, and technology integration. Business process modernization enhances efficiency through standardized digital workflows. Organizational and human resource adaptation supports the development of digital competencies and new work practices. Technology integration improves effectiveness through centralized data management, better coordination, and data-driven decision-making. This study proposes a conceptual model showing how these dimensions interact to strengthen digital governance. It highlights that successful digital transformation depends not only on technology adoption but also on the alignment of organizational processes, human capabilities, and technological infrastructure.